HUMAN RESOURCE MANAGEMENT AND LABOR RELATIONS REGULATION IN GEORGIA - Kvirkvaia, Murtaz (European Scientific Journal, ESJ, 2013)
The article reveals the problems of formation of labor relations in Georgia – an urgent topic of a constant discussion of the last two decades. The opinion difference is particularly evident referring to the Labor Code of Georgia. The article conveys views and thoughts of the interested parties and experts connected to the legislation based on regulation of labor relations. The research concentrates on a modern approach of human resources management in terms of labor relations. The work provides conclusions and recommendations fostering the formation of civilized labor relations in Georgia. The author states the Labor Code should not possess excessive significance as the adequate and correct HR management will solve a lot of problems regarding civilized labor relations.